Incidence and disease course of covid-19 infection among unvaccinated patients who received local corticosteroid injections - OKÇU, MEHMET; GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (My University, 2023)
Objective There are concerns that local corticosteroid injections may increase the risk of COVID-19 infection because of the immunosuppressive effect of corticosteroids. This study aimed to examine the relationship between local corticosteroid injections and the risk of COVID-19 infection. Design The date and type of procedure as well as the dose and type of corticosteroids used in patients who underwent local corticosteroid injections within 1 yr after the first COVID-19 case in the country were examined retrospectively and recorded. Patients who did not receive corticosteroids were included in the control group. Coronavirus disease 2019 infection histories of all patients were recorded. Results There was no significant difference between the patients who received local corticosteroids and the control group in terms of the incidence of COVID-19 infections, and the number of patients who needed hospitalization or intensive care treatment. In addition, it was found that the administration of two injections, the type of procedure performed, and the dose and type of steroids were not associated with the incidence or severity of COVID-19 infections. Conclusions It has been shown that local corticosteroid injections are not associated with the incidence of COVID-19 infections and the number of patients who need hospitalization or intensive care treatment due to COVID-19.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Corticosteroid; COVID; Epidural; Injection